Political Internet discourse as a subject of linguistic research: definition and characteristics - Bilokobylskyi, Yurii (Current issues of Ukrainian linguistics: theory and practice, 2022)
The article is devoted to the study of political discourse within the virtual space – an "artificial" world created in recent decades with the help of information technologies, where individuals are able to communicate with each other over vast distances, modeling their own personality at will. The research, in particular, is aimed at studyinh how political communication changes in the virtual reality, what linguistic and extralinguistic means are used by political actors when communicating with their electorate and between each other. Using the categories proposed by T. van Dijk, the article proposes the use of new characteristic features for Internet discourse, such as speaker’s anonymity, semi-formal tone of communication, more open and competitive expression of opinions, emotionality, etc. for the analysis of communication within the virtual space. The article proposes a clarification of the definition of political discourse, highlights its most important features, defines differences in communicative strategies depending on the gender of the speaker or political actor. With the help of the proposed categories and based on the works of such prominent scholars as R. Wodak, L. de Saussure and T. van Dijk, the article provides a new definition of the concept of political Internet discourse, which is aimed at a more complete consideration of the interaction between individuals within the virtual space. It is suggested to use the categories proposed by T. van Dijk for the analysis of communication within the virtual space, which will allow to single out communicative situations that are directly related to the political sphere. By comparing communicative situations in the "artificial" world with the physical one, it is argued that a characteristic feature of political Internet discourse is the transfer of extralinguistic components through textual communication. It is clarified that in many communicativesituations between political actors and other users, the latter act as the information recipients, limited only to the ability to interact with other recipients. In conclusion, it is suggested to understand political Internet discourse as actions of a linguistic and extralinguistic nature, related to the political sphere and implemented in the virtual space by political actors and ordinary users; actions, which are characterized by the possibility of anonymous subjectivity, semi-formality, a more open and competitive nature of expressing opinions, etc., and in which the transfer of extralinguistic components is achieved mainly through text communication. Based on the categorical clarifications made in the article, strategies for further Internet discourse analysis are developed.